تناقضات النظام الاجتماعي ونشوء علاقات الجيب العلوي داخل الأسرة الجزائرية - بن النية, عبد الإله; بن صويلح, ليليا (جامعة الوادي - University of Eloued, 2021)
نهدف من خلال هذه الورقة البحثية الى محاولة فهم النمط الجديد في ديكور العلاقات داخل نسق الأسرة –بين الزوجين- ولفت الانتباه الى التحولات الخطيرة التي يعرفها المجتمع الجزائري على مستوى العلاقات الاجتماعية الحيوية ، معتمدين في هذا المسعى على التتبع التاريخي لتطور الأسرة الجزائرية، ومحاولة استقراء التناقضات التي شابت البنية النسقية لها في كل مرحلة، إضافة الى التعرض للنقاشات النظرية حول الأسرة في التراث السوسيولوجي ومحاولة استثمار مطارحات عالم الاجتماع البولندي سيغموند باومان لتحقيق فهم أعمق لمظاهر المادية والسيولة في العلاقات داخل الأسرة الجزائرية. Abstract: Through this research paper we try to understand the new pattern of relationships within Algerian family system –between spouses-, and discuss the profound transformations that Algerian society is experiencing at the level of vital social relationships. In this endeavour, we rely on historical traces development of the Algerian family; and explore the contradictions that have comprised the system in every stage. In addition to exposure to theoretical debates about family in sociological heritage and try to capitalize on the research of the Polish sociologist Zygmunt Bauman to gain a deeper understanding of the financial and liquidity features of relations within Algerian family.
محاولة فهم سوسيولوجية
مقال
Keywords: التغير الاجتماعي ; النظام الاجتماعي ; علاقات الجيب العلوي ; الأسرة الجزائرية; Social Change; Social system; Top-Pocket Relationships; Algerian family